Challenges of collaborative governance in lifelong guidance in Finland - Tommi Wallenius; Janne Varjo (Nordic Journal of Studies in Educational Policy, 2024)
The aim of the paper was to analyse the ways in which collaborative governance appears in the context of lifelong guidance in Finland. The research question was ‘What are (in terms of problem-solving, collaborative process and multi-relational accountability) the challenges for collaborative governance of lifelong guidance in Finland?’ The analysis drew from ten in-depth thematic interviews with experts working on issues related to the governance of lifelong guidance at the central government of Finland and related interest groups. Our analysis showed that, despite the progress made, institutional structures, practices and perceptions challenge the implementation of collaborative governance. The results point out three key challenges: The first generally relates to the aim of increasing collaborative governance, the second to the creation of a collaborative network and the formation of shared objectives in lifelong guidance and the third to the concept of multi-relational accountability. A key question in addressing these challenges is how to evaluate and verify the benefits of collaborative governance.